Study of ultrasonic effect in the extraction process - Chong, Jun Tian (2022)

(untitled)
Currently, the application of ultrasonic-assisted extraction (UAE) in cellulose extraction process is widely discussed. The abundance of biomass waste such as oil palm empty fruit bunch (OPEFB) has exacerbated environmental problems and the UAE is a promising environmentally friendly technology to extract the cellulose from the OPEFB. In this research, several important parameters were varied to investigate their influences towards the cellulose extraction efficiency from the OPEFB via ultrasonication. The UAE process conducted using sonication bath was manipulated using four different processing parameters, which are sonication duration at 120 minutes, 180 minutes and 240 minutes, temperature at 30 oC, 40 oC, 50 oC for ethanol, concentration of sodium hydroxide (NaOH) solution varied from 0.5 M, 0.75 M to 1.0 M as well as different types of solvent used such as ethanol, chloroform and NaOH solution. The characterization methods involving Fourier Transform Infrared Spectroscopy (FTIR), High Performance Liquid Chromatography (HPLC) and Differential Scanning Calorimetry (DSC) were carried out to determine the ultrasonic effect in the extraction process. After various ultrasonication parameters were conducted, it was found that the treatment using 1.0 M NaOH solution at 80 oC for 180 minutes yielded the highest cellulose content from the OPEFB, 78.12 wt%. The ultrasonic-assisted alkali extraction can remove the lignin from the raw OPEFB and increase the efficiency of cellulose extraction process. To further evaluated the strength of UAE, the raw OPEFB was treated using the obtained optimum condition: temperature at 80 oC, duration of 120 minutes, 1.0 M NaOH solution. The treated sample was further converted to carboxymethyl cellulose (CMC). The conversion of CMC was successful, and the CMC provided DS value of 0.5201, which is able to form film for more applications. On the whole, the outcome is significant for the future development of UAE using OPEFB as feedstock to produce CMC at industry level.